الفطرة وأثرها، بين البناء القرآني ومعاول الهدم - لخشين, رضوان (جامعة الوادي university of eloued, 2022)
الحمد لله أولا وآخرا، وبعد: بحثنا هذا يعرض موضوعا مهما هو موضوع الفطرة من حيث تعريفها لغة وشرعا، وبيان جملة من مسائلها، فالفطرة هي الخلقة والجبلة الأولى التي جعل الله سبحانه الخليقة عليها، دينا وبدنا، وخِلقة وخُلقا، عمَّ الله سبحانه بها الناس عامة، فجعلهم عليها، بها يولدون، وفي بواطنهم مستقرها، ثم جاءت الشرائع الدينية جميعها، والملة الإسلامية بخصوصها، جاءت لبيان تلك الفطرة وبنائها وتشريع ما يحفظها ويناسبها، فكان في القرآن الكريم ما يهدي الفطرة إلى بناء أركانها وتزيين جوانبها، وتجميل جنباتها، حفاظا عليها وضمان لبقائها، تحقيقا لأركان عمارة الأرض من البقاء والعبادة، فمهما استمرت النفوس على هدي القرآن بقيت لها سلامة فطرتها، ودون ذلك وغيره إنما هو معول هدم لها، معاول بأيدي المفسدين وفي مقدمهم الشيطان اللعين، فوضح البحث كيف بنى القرآن الكريم الفطرة، وكملها وحفظها، ووضح مختلف مظاهر فسادها. Abstract : Praise be to Allah first and last, and then: This research presents the important topic of human original nature (Fitra). After defining it in both language and Sharia, it studies a number of related issues. Fitra could be defined as the morphological, religious and ethical state in which Allah created humans and made suitable and compatible legislations, especially Islamic Sharia, that preserve and consolidate it. For this aim and in fulfillment of the two pillars of the earth’s inhabitation that are survival and worship, Quran came to guide humans in constructing the pillars of Fitra and beautifying both its inner and perceptible aspects. Consequently, Fitra safety will remain fulfilled as long as the guidance of Quran is followed. Otherwise, it is only a shovel that demolishes them, shovels in the hands of the corrupters, led by the damned Satan. The research clarifies how Quran constructed, completed and consolidated Fitra, and the different indicators of its corruption
مقال
Keywords: الفطرة؛ الجبلة؛ هدم الفطرة؛ القرآن والفطرة; Fitra, building Fitra, common sense, demolishing Fitra, the Quran and Fitra